Borrowed time - Smith, Greg Leitich (Clarion Books/Houghton Mifflin Harcourt, 2015)
"In this time-travel adventure, Max Pierson-Takahashi and his friend Petra return to the days of the dinosaurs, where they must survive attacks from deadly prehistoric creatures and a vengeful, pistol-toting girl from the 1920s"--Provided by publisher.